Enoxacin ameliorates polycystic ovary syndrome by promoting the browning of white adipose tissue and restoring gut dysbiosis - Zhu, Wanlong; Fu, Liya; Xu, Changjing; Peng, Ke; Liu, Yuanzhi; Tang, Hui; Huang, Yilan; Yang, Xuping (Frontiers in Pharmacology, 2022)
Background Polycystic ovary syndrome (PCOS) has been shown to be a common complex endocrine disorder syndrome closely related to metabolism disorder, which is often accompanied by adipose dysfunction. Enoxacin, a stimulator of RNA interference, can protect against diet-induced obesity and insulin resistance by promoting fat thermogenesis. However, the treatment effect of enoxacin on PCOS has not been explicitly investigated. Method The PCOS mouse model was established by subcutaneous injection of dehydroepiandrosterone (DHEA). Serum was collected to measure sex hormones, insulin and lipids. Ovary, adipose tissue and intestinal contents were harvested for further analysis by hematoxylin-eosin staining, immunohistochemistry, RT-PCR, Western blotting and 16S rDNA sequencing. Results The present study revealed that reproductive endocrine disorder and glucose intolerance in PCOS mice induced by DHEA were attenuated by enoxacin treatment. Mechanistically, Enoxacin significantly promoted thermogenesis induced by white fat browning in PCOS mice. The 16S rDNA sequencing of the intestinal microbiome analysis indicated enoxacin alters the structure of the gut flora by increasing the abundance of genus Akkermansia and Dubosiella and by decreasing the abundance of Alistipes, Lactococcus and Lachnospiraceae_NK4A136. Conclusion Our study indicated that enoxacin ameliorates PCOS phenotype by the browning of white fat and restoring gut dysbiosis. These findings provide a novel therapeutic target for enoxacin in PCOS clinical application.